GenAI, Human Design, and Academic Roles in the Department of Library and Information Science - Rahmi; Aviazka Firdhaussi Azmir; Nina Mayesti (Universitas Pendidikan Ganesha, 2025)
The rapid development of Generative Artificial Intelligence (GenAI) in higher education has shifted the focus from mere technological access toward issues of trust and governance; however, empirical evidence regarding patterns of GenAI utilization remains limited. This study aims to analyze patterns of GenAI use, levels of trust in the technology, and to examine whether Human Design (HD) labels differentiate perceptions and practices of GenAI use in academic settings. The study employed a quantitative design using a cross-sectional survey approach. Data were collected through an online questionnaire administered to 213 respondents, consisting of students and lecturers from the Department of Library and Information Science. Data analysis was conducted using descriptive and inferential statistics, specifically one-way analysis of variance (ANOVA), across five main constructs: academic performance, prior experience, personal perceptions, technical knowledge, and trust in technology. The results indicate that GenAI has been routinely used at an early to intermediate stage of integration, primarily for ideation and academic drafting activities. Respondents demonstrated a “competent yet critical” attitude, with relatively low levels of trust in terms of accuracy and privacy. Furthermore, the HD labels did not reveal significant differences across all analyzed constructs. This study concludes that trust in technology is a key factor shaping the quality of academic engagement with GenAI; therefore, strengthening verification-centered literacies and inclusive privacy policies is essential to promote responsible GenAI adoption in higher education.